2003
DOI: 10.1210/jc.2003-030527
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Status in Patients with Optic Nerve Hypoplasia: Relationship to Midline Central Nervous System Abnormalities and Appearance of the Hypothalamic-Pituitary Axis on Magnetic Resonance Imaging

Abstract: We here: 1) describe the phenotypic spectrum, including magnetic resonance imaging (MRI) appearances of the pituitary stalk and anterior and posterior pituitary [H-P (hypothalamic-pituitary) axis], in children with optic nerve hypoplasia (ONH) with or without an abnormal septum pellucidum (SP); and 2) define endocrine dysfunction according to the MRI findings. Medical records of 55 children with ONH who had been assessed by ophthalmology and endocrine services were reviewed. All had MRI of the brain and H-P ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 25 publications
9
78
2
2
Order By: Relevance
“…Cerebellar hypoplasia, schizencephaly, aplasia of the fornix, encephalocele, and cortical dysplasia were also reported in SOD patients [1][2][3]. In addition, neurological symptoms are frequently observed, including mental retardation, epilepsy, and communicative or behavioral difficulties [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cerebellar hypoplasia, schizencephaly, aplasia of the fornix, encephalocele, and cortical dysplasia were also reported in SOD patients [1][2][3]. In addition, neurological symptoms are frequently observed, including mental retardation, epilepsy, and communicative or behavioral difficulties [1].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of SOD is made based on the presence of 2 or more features of the classic triad: (i) optic nerve hypoplasia, (ii) hypopituitarism, ranging from isolated to multiple hormone deficiency, and (iii) midline brain defects (1). However, SOD is heterogeneous and may accompany other brain anomalies and developmental delay [1,2]. Regarding pubertal disturbance, patients with SOD usually show gonadotropin deficiency as a manifestation of hypopituitarism; however, it has been reported that several patients showed central precocious puberty [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants with abnormal brain development can be at risk for hypothalamic dysfunction leading to pituitary insufficiency, and early manifestations of endocrine dysfunction might not be detected by routine newborn screening (28). Thyroid screening, including measurement of thyroid stimulation hormone (TSH) and thyroxine (either free T4 or both total T4 and estimated free T4) should be performed at age 2 weeks and again at age 3 months.…”
Section: Outpatient Management Of Infants With Laboratory Evidence Ofmentioning
confidence: 99%
“…However only 30% of cases present the complete triad 2 and almost 40% of SOD patients may present with normal endocrinology 3 . We describe MRI and CT findings in a patient with SOD characterized by vascular abnormalities, emphasizing the correlation between SOD and a vascular disruption that may occur during embryologic development.…”
Section: Introductionmentioning
confidence: 99%